Relaxation and Cold Compress Effectiveness toward Labor Pain Intensity During of the First Stage - Handayani, Lulut (International Journal of Psychosocial Rehabilitation, 2020)
Background Pain is an integral part of the delivery. The reduction of labor pain is needed to break the cycle of pain with all the impact. Nonpharmacologic pain management is preferred because it is inexpensive, safe, can be done by the family. Research purposes Want to know the effectiveness of deep breathing relaxation plus cold compress than relaxation breath in any of the first stage of labor pain relief the active phase. Method This study research design Quasi Eksperimet Design with non-randomized control group pretest- posttest design. The research instrument is wineskins ice, cold jelly bag, and scale of 0-10 Numeric Rating Scale (NRS). Subject Maternal active phase of the first stage meet inclusion and exclusion criteria. Result Pain intensity respondent before giving relaxation deep breathing plus cold compress all (100%) experienced severe pain and moderate pain while after the administration of relaxation deep breathing plus cold compress all (100%) of respondents experienced moderate pain and mild pain and no pain severe, Paired T-test results found no significant difference in pain intensity before and after the intervention (p = 0.000 and 95% confidence interval), it means that there is a significant effect of granting relaxation deep breath and a cold compress to the intensity of pain in women giving birth when I. Impairment the average intensity of pain before and after administration of relaxation and breath in the cold compress of 1.86. The results of the correlation between two variables are equal to 0801 with a sig of 0000. Conclusion Relaxation is a psychological modulation coupled with a cold pack that is a sensory modulation affecting the reduction of pain greater than the use of one method that is relaxation. The use of two methods in reducing labor pain is more effective because the effect of the method is further reinforced by the effects of other methods.